2015
DOI: 10.1016/s0924-9338(15)31954-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Some Psychological Factors in Psoriatic Patients

Abstract: BackgroundPsoriasis is a disease which may have direct impact on the psychological and social aspects, particularly due to its visibility. To date, we are unaware of any study showing relationship between psoriasis and psychological parameters such as psychological vulnerability and coping strategies.Objectiveto evaluate the effects of psoriasis on some psychological parameters in an Iranian population.MethodsPatients having histopathologically confirmed psoriasis for at least 6 months attending the Clinic of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
(14 reference statements)
1
3
0
Order By: Relevance
“…Many studies showed that with effective acne treatment, symptoms of anxiety and depression can be reduced and quality of life can be improved. 4,12,15,16 Similarly, our data showed that AQOLS increased significantly after the acne treatment. The relationship between isotretinoin and depression is still a controversial issue although studies are reporting a relationship.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Many studies showed that with effective acne treatment, symptoms of anxiety and depression can be reduced and quality of life can be improved. 4,12,15,16 Similarly, our data showed that AQOLS increased significantly after the acne treatment. The relationship between isotretinoin and depression is still a controversial issue although studies are reporting a relationship.…”
Section: Discussionsupporting
confidence: 77%
“…Acne, which is a young adult disease and one of the most common causes of dermatology clinic visits, reduces the quality of life by causing psychiatric disorders such as depression, anxiety, low self-esteem, and social phobia. 4 These negative psychological effects are more significant in female patients and patients with facial involvement. Kellett and Gawkrodger reported that acne caused more psychological problems in female patients, and Aktan et al reported that anxiety levels were higher in females than in males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depression ratings decreased from three to six months of treatment. Fakour et al (2014) found statistically significant increases in depression measured with the BDI in 98 acne patients treated with isotretinoin, although quality of life overall was improved. Ormerod et al (2012) found a trend level of increase on the BDI which was concerning as there were only 17 patients, although processing speeds improved on cognitive tasks.…”
Section: Isotretinoin Treatment Studies In Acne Patientsmentioning
confidence: 86%